Poor serum uric acid control increases risk for developing hypertension: a retrospective cohort study in China - Lin, Zeyin; Wu, Shaoyan; Chen, Zhe; Luo, Weijian; Lin, Zhihui; Su, Honghui; Guo, Dongming (Frontiers in Endocrinology, 2024)
Background: Serum uric acid (SUA) has been suggested as a contributor of hypertension. However, reports on the relationship between changes in SUA and hypertension are limited. Hence, we aimed to investigate the potential impact of SUA, especially its change over time, on hypertension incidence.This dynamic cohort included 6052 participants without hypertension at baseline. Participants were categorized into six grades based on whether baseline SUA was high and whether changes in SUA progressed to hyperuricemia or decreased to normal levels. Grades 1 to 6 represented the participants' SUA control from best to worst. Logistic regression and restricted cubic spline (RCS) models were used to explore the association of the grades of SUA control and hypertension incidence.Results: During a median follow-up of 6 years, 2550 (42.1%) participants developed hypertension. After adjusting confounding factors, compared to grade 1 with the best control of SUA, the odds ratios for grades 2 to 6 with worse control were 1.347 (1.109-1.636), 1.138 (0.764-1.693), 1.552 (1.245-1.934), 1.765 (1.170-2.663), and 2.165 (1.566-2.993), respectively. RCS indicated a linear correlation between the risk of hypertension and changes in SUA, and an elevated risk in participants with baseline hyperuricemia. Subgroup analyses showed that grades of SUA control had an interaction with systolic (P = 0.003) and diastolic blood pressure (P < 0.001). Sensitivity analyses further determined the robustness of the result that participants with poor SUA control have a higher risk of developing hypertension.Poor SUA control, an increase in SUA over time, rises the risk of developing hypertension regardless of whether the initial SUA is normal or not. Initial hyperuricemia will exacerbate this risk. Effective SUA control should be an important measure for primary prevention of hypertension.